Value of PET imaging for radiation therapy - Lapa, Constantin Frederik Victor; Nestle, Ursula; Albert, Nathalie L.; Baues, Christian; Beer, Ambros; Buck, Andreas; Budach, Volker; Bütof, Rebecca; Combs, Stephanie E.; Derlin, Thorsten; Eiber, Matthias; Fendler, Wolfgang P.; et al. (Strahlentherapie und Onkologie, 2021)
This comprehensive review written by experts in their field gives an overview on the current status of incorporating positron emission tomography (PET) into radiation treatment planning. Moreover, it highlights ongoing studies for treatment individualisation and per-treatment tumour response monitoring for various primary tumours. Novel tracers and image analysis methods are discussed. The authors believe this contribution to be of crucial value for experts in the field as well as for policy makers deciding on the reimbursement of this powerful imaging modality.
Gesehen am 15.12.2021